Top 100 Cited Research of Confirmatory Factor Analysis (CFA) in Education From 2012 to 2021 - Mila Candra Pristianti (International Journal of Current Educational Research, 2022)
The aim of this research is to analyze the trends and future research opportunities related to confirmatory factor analysis in education. This research uses a descriptive bibliometric analysis and literature review to determine research trends. The data in this research used the Scopus database during 2012-2021. Data in form .CSV was analyzed using Ms. Excel and data in form .RIS was analyzed using VOSviewer. The conclusion from this research are the trend of research on this topic has increased every year in the last ten years. The most widely used keyword is confirmatory factor analysis. Research related to CFA in education has a wide and good opportunity to be carried out for several reasons including: (1) the trend shows a good graph and continues to increase; (2) the number of citations per paper per year shows a number with a high average; (3) From many studies, it is stated that CFA has a contribution in educational research. For future research, we can focus on discussing CFA in a multidisciplinary manner or discussing CFA trends in education using databases other than Scopus.